Memperkuat Kebijakan Negara Dalam Penanggulangan Radikalisme di Lembaga Pendidikan - Abdul Aziz (Hikmah: Journal of Islamic Studies, 2016)
Abstract Educational institutions are considered as a long term strategic instruments in overcoming the problem of violence and religious radicalismwhichburstinthepostofpoliticalreformation. Creating the certainty of education process been positively is equal to ensure the futureoftheyoungergenerationasthesuccessortothenation’s development. Therefore, educational institutions should be able to create a generation of peace. It is should be a collective duty and obligation to build a breaker movement of radicalism regeneration among young people through education process which is done by strengthening and structuring the understanding of knowledges in various disciplines that studied by pupils and students. So what have to arrange and aligne is not only subjects or study of religion particularly, but all of sources and courses need to be delivered in a humanists and tolerant approach based on strengthening the mental and character nationalism of pupils and students. This paper will attempt to review some aspects that could beadoptedby government in order to face the threat of radicalism phenomenon of the youth in educational institutions. Before the main focus, the discussion will be conducted by conceptualization of the problem. This conceptualization begins with an understanding of the concept of religious radicalism, followed by understanding the concept of intolerance. While in the main focus the discussion will surfaces three strategic policy of the state namely strengthening the ideology of of tolerance, the revitalization of the values of Pancasila, and the empowerment of civil society, and finally the conclusion. Keyword: Policy, Youth, Tolerance, violence. Abstrak Lembaga pendidikan dianggap sebagai alat yang strategi untuk jangka panjang dalam mengatasi permasalahan tentang kekerasan dan radikalisme agama yang ramai pada paska reformasi politik. Menciptakan kepastian dari proses pendidikan secara positif itu sama seperti mengukur masa depan para generasi muda sebagai penerus pembangunan bangsa. Oleh karena itu, lembaga pendidikan seharusnya dapat menciptakan generasi perdamaian. Hal tersebut seharusnya menjadi tugas kolektif dan kewajiban untuk membangun gerakan pemecah dari regenerasi radikalisasi diantara generasi muda melalui proses pendidikan yang dilakukan melalui penguatan dan penataan dalam memahami ilmu di berbagai disiplin ilmu yang dipelajar oleh para siswa dan mahasiswa. Sehingga apa yang harus diatur dan diselaraskan tidak hanya mata pelajaran ataupun pelajaran agama khususnya. Tetapi semua sumber dan mata kuliah perlu disampaikan secara humanis dan pendekatan toleransi berdasarkan penguatan mental dan karakter siswa dan mahasiswa. Tulisan ini akan mencoba mengulas beberapa aspek yang bisa diadopsi oleh pemerintah dalam rangka menghadapi ancaman fenomena radikalisme pada kaum muda di lembaga pendidikan. Sebelum fokus pada poin utama, pembahasan akan dilakukan dengan masalah konseptualisasi. Konseptualisasi tersebut dimulai dengan pemahaman tentang konsep radikalisasi agama, diikuti dengan pemahaman konsep toleransi. Sementara di poin utama, pembahasan akan muncul 3 kebijakan strategi Negara yaitu penguatan ideologi toleransi, dan revitalisasi nilai-nilai Pancasila, dan pemberdayaan masyarakat sipil, dan akhirnya kesimpulan. Kata Kunci: Kebijakan, Pemuda, Toleransi, Kekerasan